Characterization of synthetic promoters in relation to protein expression in escherichia coli. - Fong, Huay Ning. (2013)
Promoters are one of the building blocks of a synthetically engineered biological system. Within a synthetically engineered biological system, they are involved in processes at the transcriptional level as they are responsible for the initiation of the transcription in gene expressions. The purpose of the study is to find effective and efficient ways to characterize the promoters so that it may be used in a predictable manner in future to aid researchers in designing novel synthetic genetic circuits.